PTH-062 Treating TPMT Deficient Patients with Thiopurines: A Tertiary IBD Centre Experience. (17th August 2016) - Johnston, EL; Warner, BD; Fong, SC; Blaker, PA; Arenas-Hernandez, M; Marinaki, TM; Anderson, S; Irving, PM; Sanderson, JD
Abstract : Introduction: Thiopurine S-methyltransferase (TPMT) activity is inherited, with around 1 in 300 Caucasian individuals being deficient. Patients with zero TPMT activity are at risk of severe myelosuppression if given standard doses of thiopurines (TP), therefore TP are rarely prescribed. Our unit has treated a small number of these patients with 5–10% of the standard dose. Our experience was evaluated. Methods: All patients with TPMT deficiency (enzyme activity <10 pmol/h/mgHb or genotyped as homozygote for deficiency associated alleles) detected between July 2002 and April 2015 were identified. Drug tolerability, TGN profile and long-term outcomes were assessed. Results: 23 TPMT deficient patients (8 from Gastroenterology) were identified from 7100 patients. 5 (22%) patients were treated with TP, all of whom had inflammatory bowel disease. Patient 1–32 yr old Caucasian female with ileocolonic Crohn's disease (CD) referred from another centre (TPMT 1). She was prescribed 50 mg/day mercaptopurine (MP) (0.66 mg/kg) before her TPMT was checked. After 10 days she developed severe pancytopenia (Hb 74 g/L, WCC 1.8x10 9 /L, Plts 62x10 9 /L) requiring hospital admission. She made a full recovery after cessation of the drug and is now in remission on infliximab. Patient 2–56 yr old Caucasian male with ileal and perianal CD (TPMT 2). He was prescribed 2.5 mg/day azathioprine (Aza) (0.03 mg/kg) for 1 year with normal FBC and liver function tests. His mean TGNs were sub therapeutic at 161 pmol/mL (normal range 235–450 pmol/8x108 8 RBC). He continued to have active disease despite Aza and was switched to methotrexate (MTX). Patient 3–47 yr old black, African female with pan-ulcerative colitis (UC) (TPMT 9). She was prescribed 10 mg/day Aza (0.11 mg/kg), which was increased to 20 mg/day (0.22 mg/kg) after 2 months because of sub therapeutic TGNs (83 pmol/mL). After the dose increase she developed drug-induced hepatitis with ALT 378 IU/L. The Aza was switched to MTX and the hepatitis resolved. Patient 4–32 yr old Caucasian female with pan-UC (TPMT 0). She was prescribed 12.5 mg/alternate days MP (0.1 mg/kg/day) which was decreased to 12.5 mg twice a week (0.06 mg/kg/day) due to supratherapuetic TGNs (1816 pmol/mL). Her FBC and liver function tests were normal but she continued to have active disease and has recently started on anti-TNF therapy. Patient 5–49 yr old Caucasian male with pouchitis after a pan-proctocolectomy for UC (TPMT genotype *3 A/*3 C). He was prescribed Aza 5 mg/day (0.07 mg/kg) with normal FBC and slightly supra therapeutic TGNs (695 pmol/mL). He continued to have active disease after 6 months so Aza was stopped and starting MTX was advised. Conclusion: In this small cohort of patients, treatment with thiopurines failed to achieve clinical remission, despite aiming for therapeutic TGNs in 3 patients. Patients prescribed ≤5% of the recommended dose tolerated the drug well but pancytopenia and drug induced hepatitis occurred in doses above that. Low doses of TP may be considered with careful blood monitoring, particularly FBC, however other treatments are likely to be more beneficial to induce and maintain remission of CD and moderate to severe UC. Disclosure of Interest: None Declared